2022
DOI: 10.1002/hyp.14522
|View full text |Cite
|
Sign up to set email alerts
|

The effect of crab burrows on soil‐water dynamics in mangroves

Abstract: Many mangrove ecosystem services, such as carbon sequestration, are closely linked to mangrove soil water content, which in turn is thought to depend on animal burrow density and the properties of the sediment in which the burrows are constructed. We measured the water content in the sediment matrix between crab burrows across 26 plots in a typical, fine‐grained (clay), mangrove soil in the Mekong Delta, Vietnam. We found that the water content of the sediment matrix remained more or less constant throughout t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 35 publications
1
4
0
Order By: Relevance
“…This result may provide explanation for the field observations conducted by Arnaud et al. (2022), that the impact of crab burrows on groundwater drainage in the salt marsh cannot be easily observed.…”
Section: Resultssupporting
confidence: 62%
See 3 more Smart Citations
“…This result may provide explanation for the field observations conducted by Arnaud et al. (2022), that the impact of crab burrows on groundwater drainage in the salt marsh cannot be easily observed.…”
Section: Resultssupporting
confidence: 62%
“…Note that even in the burrowed marsh, the lowest saturation in the sediment at the monitor location (x = 2.555 m. z = 0.9 m) was 0.97, indicating only 3% porewater has been drained. This result may provide explanation for the field observations conducted by Arnaud et al (2022), that the impact of crab burrows on groundwater drainage in the salt marsh cannot be easily observed.…”
Section: Soil Aerationmentioning
confidence: 60%
See 2 more Smart Citations
“…In natural salt marshes, macropores are irregular in geometry and depth. As reported by Arnaud et al (2022), macropores may have more than one opening and connect the marsh platform to tidal creeks, resulting in complex water exchange between macropores and surrounding soil. In addition, it has been reported that the impact of salt precipitation on evaporation is related to the type of efflorescence (i.e., crusty and patchy) (Eloukabi et al, 2013).…”
Section: Discussionmentioning
confidence: 96%